(untitled) (Journal of Hama University, 2019)
The research aims to use the flexible budget in evaluation Performance and decision making, and the difference between it and the fixed budget information and their impact on decision making. The research depend on the descriptive approach and the study of the case of the Syrian Company for Cement and Building Materials in Hama Governorate for Laboratory No. 2 of 2017, The data for the research was collected through the company’s cost lists for 2017, planning department information ,through the field visit, interviews with the engineers and production manager. To test the hypotheses of the research, the performance of the company was evaluated by comparing the actual results with the results of the flexible budget and the fixed budget. The following results were obtained: The results of the flexible budget show that the company has the efficiency in exploiting available resources and that deviations of cost elements are positive and did not exceed the quantities specified for them, except for Gypsum and Bozlana material, are negative deviations due to a deviation in the quantity of these materials due to the waste during the production process and the lack of purity of raw materials (Gypsum and Bozlana). However the fixed budget shows those deviations positive, and finds that the company does not achieve the target of the planned production of cement, which is 330000 tons of cement, due to the weakness of the cement marketing process. Thus the application of flexible budget has helped to evaluate the performance of the laboratory and provide information based on the decision making process is true, and can not rely on the fixed budget because it gives misleading results to evaluate performance and decision making.